PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT SOLO MURNI (STUDI KASUS PADA BAGIAN PRODUKSI) - Lutfan Danu Saputro; Apriatni Endang Prihatini (Universitas Diponegoro, 2018)
Today's increasingly fierce business competition encourages companies to have the competence to grow and compete with other companies. To improve the quality, the company must be able to understand the desire of employees which to get employees who have high job satisfaction on their own. There is an increase of employees who come out every year during the last three years, it is assumed that there is a problem about job satisfaction within the employee in the production of PT SOLO MURNI. Implementation of occupational safety and health (OHS) program is important because a safe working environment can affect employee job satisfaction (gilmer, 1996). In addition, the provision of compensation with fair and reasonable principles allows employees to meet all their needs so that will lead to job satisfaction (Hasibuhan, 2016). The purpose of this study is to know the effect of OHS variables and compensation on employee job satisfaction. The methods used to process the data are qualitative analysis method, quantitative analysis, data quality test, correlation test, regression test, and significance test with help from SPSS 16 for windows. The results of the test show that OHS and compensation affect partially and simultaneously to employee job satisfaction. Simultaneously OHS and compensation effect on employee job satisfaction equal to the coefficient of determination 33,1%. Based on the results of multiple linear tests OHS has the greatest influence on employee job satisfaction with a significance of 0.03. PT SOLO MURNI is expected to complete the personal protective equipment, renew personal protective equipment with the highest quality, and increase health insurance by establishing clinics within the company area, in order to increase employee job satisfaction.